Unternehmensinterne Organisation internationaler Arbeitsteilung: Industrielle Forschungs- und Entwicklungsorganisation als Form und Träger von Globalisierungsprozessen - Hack, Lothar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
Debates on globalization are, quite often, concerned with the tensions between world market and nation-state. It might give a much more realistic picture to include, as a third pole, the global companies with their internal organizational structures, which incorporate quite important aspects of the international division of labour. This can be demonstrated by the increasing global organization of industrial R&D as well as, more generally, by the new modes of the organization of competence, as might be seen in Centers of Competence, Cross-funcional teams etc.